(untitled) (Nigerian Journal of Technology, 2020)
A reddish-brown laterite was treated with up to 14 % oil palm empty fruit bunch ash (EFBA) by dry weight of soil and compacted with the British Standard light, BSL (or Standard Proctor) compactive effort. Index, compaction, strength and durability tests as well as microanalysis of the natural and stabilized specimens were carried out. The index, compaction characteristics (maximum dry density, MDD and optimum moisture content, OMC) and strength properties (California bearing ratio, CBR and unconfined compressive strength, UCS) were improved with higher EFBA treatment. Peak un-soaked and soaked CBR values of 70.0 and 45.0 %, as well as peak UCS strengths of 253.0, 462.0 and 577 kN/m2 at 7, 14 and 28 days curing were recorded at 8 % EFBA content. Based on the CBR specification specified in the Nigerian General Specifications, the laterite optimally treated with 8 % EFBA compacted with the BSL compactive effort can be used as a fill material in the construction of low-volume traffic pavement. The benefit of the EFBA application is primarily the reduction of the adverse environmental impact of the oil palm empty fruit bunch waste. http://dx.doi.org/10.4314/njt.v39i3.10